Impacto do tratamento odontológico na qualidade de vida relacionada à saúde bucal de adolescentes: uma abordagem quantitativa e qualitativa - Maroneze, Marília Cunha (2017)
The assessment of the impact of dental treatment on adolescents must include measures that are capable of quantifying and understand the subjective functional, social, and emotional well-being aspects reported by the patients. It also must be able to comprise how oral interventions can modify the daily life and the oral health related quality of life (OHRQoL) of these individuals. The aim of this study was to evaluate and understand the impact of dental treatment on the oral health related quality of life (OHRQoL) of adolescents, using a sequential mixed methods design. A sample of individuals aged 11 to 15 years-old who finished their dental treatment in the Adolescent Dental Clinic of the Federal University of Santa Maria from 2010 to 2016 were included in this study. Socioeconomic and treatment information were collected through self-administered questionnaires and clinical records of each patient, respectively. In the quantitative phase the individuals answered the short form of the Child Perception Questionnaire11-14 in two moments: before the beginning of the dental treatment and one month after the conclusion of the treatment. Paired t-tests were used and the effect size was calculated to assess the statistical significance and the magnitude of change. The qualitative evaluation was performed only after the end of the dental treatment through semi-structured questions performed flexibly, using an audio recorder, based on the dimensions of the CPQ and the answers obtained during the pilot study. The number of interviews was determined by saturation procedures and the reports were analyzed according to thematic analysis following Braun and Clarke. A total of 182 adolescents participated in the study. The effects sizes ranged from 0.35 (small) to 1.00 (large) and the oral symptoms domain presented the greatest effect. Sixteen interviews were conducted in the qualitative phase and five themes emerged from the interviews: concept of quality of life, perception of oral health, the search of service, implications of oral problems in adolescents' daily life, non-supportive environment and supportive environment. The integration of the results showed that after dental treatment the adolescents stopped reporting oral and functional problems and there was an increase in their self-esteem and their social well-being. Therefore, dental interventions should be encouraged in the adolescence because they are able to improve the OHRQoL of these individuals.